SOME COMMENTS ON FOREIGN LANGUAGE TEACHING IN PRESCHOOL EDUCATIONAL INSTITUTIONS (Archive of Conferences, 2021)
In accordance with the Resolution of the President of the Republic of Uzbekistan No. PP-5117 of May 19, 2021 on measures to bring the promotion of foreign language learning in the Republic of Uzbekistan to a qualitatively new level [1]. The Ministry of Preschool Education, in cooperation with UNICEF, has been tasked with developing and implementing a manual on teaching foreign languages to children under 7 years of age. The urgent task facing the pre-school education system of the Republic of Uzbekistan is to bring up and bring up people who are fully developed, talented, loyal to their homeland and people.